2020
DOI: 10.3390/plants9111453
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost Degradation Leads to Biomass and Species Richness Decreases on the Northeastern Qinghai-Tibet Plateau

Abstract: Degradation of permafrost with a thin overlying active layer can greatly affect vegetation via changes in the soil water and nutrient regimes within the active layer, while little is known about the presence or absence of such effects in areas with a deep active layer. Here, we selected the northeastern Qinghai-Tibet Plateau as the study area. We examined the vegetation communities and biomass along an active layer thickness (ALT) gradient from 0.6 to 3.5 m. Our results showed that plant cover, below-ground bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…By the end of the 21st century, permafrost in the Xing'anling Mountains would degrade dramatically due to climate warming, as shown in Figure 4. In the Northern Hemisphere, there is a symbiotic relationship between permafrost and wetlands; permafrost acts as a waterproof barrier, which holds water for wetland plant growth (Jin et al, 2008; Jin et al, 2020; Jin, Jin, Iwahana, et al, 2020). Our result shows that, as the key factor affecting the distribution of the most common wetland plant community in the Xing'anling Mountains, projected permafrost degradation plays a significant role in future wetland loss.…”
Section: Discussionmentioning
confidence: 99%
“…By the end of the 21st century, permafrost in the Xing'anling Mountains would degrade dramatically due to climate warming, as shown in Figure 4. In the Northern Hemisphere, there is a symbiotic relationship between permafrost and wetlands; permafrost acts as a waterproof barrier, which holds water for wetland plant growth (Jin et al, 2008; Jin et al, 2020; Jin, Jin, Iwahana, et al, 2020). Our result shows that, as the key factor affecting the distribution of the most common wetland plant community in the Xing'anling Mountains, projected permafrost degradation plays a significant role in future wetland loss.…”
Section: Discussionmentioning
confidence: 99%
“…Permafrost degradation dries the wetlands and surface soils, causing the decrease in wet species and the expansion of drought‐tolerant plants, turning the alpine meadow into the alpine desert steppe 19 . A vegetation assessment study from the HAYR showed declining plant cover, below‐ground biomass, and species richness in response to the deepening active layer 75 …”
Section: Discussionmentioning
confidence: 99%
“…Its climate is cold and humid, with a long winter and no summer. The annual average temperature is 1.1 °C, and the annual rainfall is 615 mm [ 38 , 39 , 40 ]. The altitude of the study area is 3440 m, and the geographical coordinates are 33°55′ N, 102°09′ E. According to the vegetation coverage and quicksand area, desertified grasslands were divided into light desertified grassland (LD), moderate desertified grassland (MD), severe desertified grassland (SD) and extreme desertified grassland (ED) ( Figure 1 , Table 1 ) [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%